Prevalence of Thyroid Eye Disease Among Thyroid Disorder Patients - Ramakrishna , Abinaya; Veeramani , Panimalar A; R, Akash (International Journal of Membrane Science and Technology, 2023)
Aim: To assess the prevalence of Thyroid Eye Disease among thyroid disorder patients. Introduction: Thyroid Eye Disease (TED) is a debilitating autoimmune disorder seen in hyperthyroid, hypothyroid and euthyroid patients. The global prevalence of TED is estimated to be 16 per 100,000 women and 2.9 per 100,000 men in the general population. Common symptoms include dry eyes, eyelid retraction, excessive watering, conjunctival redness and swelling, retro-orbital pain and blurred vision. This study aims to assess the prevalence of TED among dysthyroid patients attending Saveetha Medical College and Hospital, Chennai. Methodolody: The purpose of this study is to find the prevalence of TED among dysthyroid patients attending Saveetha Medical College and Hospital, Chennai during the months of July and August. A detailed history of each patient was taken after which a series of tests were conducted to identify and classify the severity of TED. This was done using NOSPECS (no signs, only signs, soft tissue involvement, proptosis, extraocular muscle involvement, corneal involvement, sight loss) classification. Schirmers test was performed to assess the prevalence of dry eyes among TED patients. Result: 122 patients consisting of 87 females and 35 males were included in this study. 43% (53 patients) were found to have Thyroid Eye Disease. There was no significant difference in prevalence between male and female subjects (43.6% and 42.8% respectively). The presence of TED was far greater in hyperthyroid than in hypothyroid patients. 44 out of 53 patients with TED were hyperthyroid (83%), 7 were hypothyroid (13.2%), and 2 patients were euthyroid (3.7%) . Schirmers test conducted on each patient revealed that 12% of the TED patients suffered from dry eyes. NCT test conducted to find the intraocular pressure in TED patients revealed no significant results. Conclusion: The high prevalence of TED seen in dysthyroid patients in this study calls for increased awareness regarding ocular manifestations in thyroid disorders. Patients should be encouraged to undergo regular checkups to ensure normal functioning of eyes and to prevent progression of the disease.